Retrospective evaluation of all recorded horse race starts in Switzerland during a four year period focusing on discipline‐specific risk factors for clinical events. (18th November 2015) - Schweizer, C.; Ramseyer, A.; Gerber, V.; Christen, G.; Burger, D.; Wohlfender, F. D.
Summary: Reasons for performing study: Racetrack injuries are of welfare concern and the prevention of injuries is an important goal in many racing jurisdictions. Over the years this has led to more detailed recording of clinical events on racecourses. However, risk factor analyses of clinical events at race meetings have not been previously reported for Switzerland. Objectives: To identify discipline‐specific factors that influence the occurrence of clinical events during race meetings with the ultimate aim of improving the monitoring and safety of racetracks in Switzerland and optimising racehorse welfare. Study design: Retrospective study of horse race data collected by the Swiss horse racing association. Methods: All race starts (n = 17, 670, including 6198 flat, 1257 obstacle and 10, 215 trot race starts) recorded over a period of 4 years (2009–2012) were analysed in multivariable mixed effect logistic regression models including horse and racecourse related data. The models were designed to identify discipline‐specific factors influencing the occurrence of clinical events on racecourses in Switzerland. Results: Factors influencing the risk of clinical events during races were different for each discipline. The risk of a clinical event in trot racing was lower for racing on a Porphyre sand track than on grass tracks. Horses whose driver was also their trainer had an approximately 2‐fold higher risk for clinical events. In obstacle races, longer distances (2401–3300 m and 3301–5400 m, respectively) had a protective effect compared with racing over shorter distances. In flat racing, 5 racecourses reported significantly fewer clinical events. In all 3 disciplines, finishing 8th place or later was associated with clinical events. Conclusions: Changes in management that aim to improve the safety and welfare of racehorses, such as racetrack adaptations, need to be individualised for each discipline.